CNS infections in childhood - Arushi Gahlot Saini; Pratibha Singhi (Wolters Kluwer Medknow Publications, 2015)
Despite advances in diagnostic techniques and management, childhood central nervous system infections contribute substantially to the burden of emergency and intensive care as well as neurodisabilityparticularly in resource-limited countries. These children often present as serious medical emergencies and need early and appropriate intensive care to reduce the immediate mortality and long-term neurological morbidity. The common clinical syndromes are acute and subacute or chronic meningitis, acute encephalitis, encephalopathy with systemic infections and post-infectious syndromes including demyelination. Early and optimal cerebrospinal fluid analysis and Neuroimaging plays are important for differential diagnosis and management of central nervous system infections and then? complications. In the emergency room, initial priorities include management of the airway, breathing, and circulation followed by prompt diagnosis and early appropriate antibiotic therapy. Prompt empiric therapy based on the age of the patient, presence of specific predisposing or high-risk factors, and the local antibiotic resistance pattern is the key to contain primary brain injury. Intensive care of these patients aims to minimise secondary brain injury with effective management of airway, breating, circulation, reversal of shock (seen in nearly 15% cases), and prompt control of raised intracranial pressure, and seizures and status epilepticus.